2022
DOI: 10.1088/1674-1056/ac7b1b
|View full text |Cite
|
Sign up to set email alerts
|

Computational studies on magnetism and ferroelectricity

Abstract: Magnetics, ferroelectrics and multiferroics have attracted great attentions because they are not only extremely important for investigating fundamental physics, but also have important applications in information technology. Here, recent computational studies on magnetism and ferroelectricity are reviewed. We first give a brief introduction to magnets, ferroelectrics, and multiferroics. Then, theoretical models and corresponding computational methods for investigating these materials are presented. In particul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 100 publications
(197 reference statements)
0
2
0
1
Order By: Relevance
“…, 其中 不 再满足原胞的周期性边界条件, 我们称其为磁周期 性边界条件(MPBC) [112] . 该定理说明波函数在磁 场下的平移会带来一个依赖于规范的相位, 这是磁 平移对称性的体现 [114,115] . 同时可注意到, 密度即 波函数的模方仍然是周期的, 与零场情况相同.…”
Section: 含磁矢势的周期性体系计算unclassified
“…, 其中 不 再满足原胞的周期性边界条件, 我们称其为磁周期 性边界条件(MPBC) [112] . 该定理说明波函数在磁 场下的平移会带来一个依赖于规范的相位, 这是磁 平移对称性的体现 [114,115] . 同时可注意到, 密度即 波函数的模方仍然是周期的, 与零场情况相同.…”
Section: 含磁矢势的周期性体系计算unclassified
“…16−18 It was found that the self-closing pore temperature was influenced by the SEI film formation and the composition of the raw material. 19 Oppositely, Celgard 2400 showed a shrinkage dimension in the longitudinal direction at 140 °C owing to its uniaxial tensile molding. 20 However, it appeared as a transparent gel at 180 °C and corresponded to the endothermic peak at 161 °C (Figure 2c), thus resulting in a short circuit.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In particular, a new first principles method is presented for computing the linear magnetoelectric coupling tensor without applying an external field. [3] Du and Wang present recent progress in magnetic skyrmions, from both theoretical and experimental aspects, with an outlook of the fundamental challenges in device applications in spintronics. [4] In experimental condensed matter physics, Li et al present an overview of recent scan-ning tunneling microscopy (STM) studies on the Majorana zero modes in iron-based superconductors.…”
mentioning
confidence: 99%